Wellington's earthquake resilience: Lessons from the 2016 Kaikōura earthquake. Issue 3 (August 2020) - Cubrinovski, Misko; Bradley, Brendon A; Elwood, Kenneth J; Johnston, David; Orchiston, Caroline; Sullivan, Timothy; Wotherspoon, Liam M
Wellington city, the capital of New Zealand, experienced substantial damage and impacts from the 2016 Kaikōura earthquake, despite its relatively large distance of 60 km from the source of the earthquake. This article draws on impact observations from this event to discuss critical issues for Wellington's earthquake resilience. Ground motion characteristics exhibiting substantial amplifications in native and reclaimed sites, including basin effects, liquefaction of reclaimed land at the port of Wellington, characteristic structural and non-structural damage to mid- and high-rise buildings, and socio-economic impacts on community are explored in detail. The main thrust of the article is to discuss implications of these observations, identify needs, and stimulate actions across a wide range of earthquake science, earthquake engineering, and socio-economic disciplines to achieve adequate resilience levels for Wellington, and other cities facing similar seismic risks.